Superlatives, clickbaits, appeals to authority, poor grammar, or boldface: Is editorial style related to the credibility of online health messages? - Greškovičová, Katarína; Masaryk, Radomír; Synak, Nikola; Čavojová, Vladimíra (Frontiers in Psychology, 2022)
Adolescents, as active online searchers, have easy access to health information. Much health information they encounter online is of poor quality and even contains potentially harmful health information. The ability to identify the quality of health messages disseminated via online technologies is needed in terms of health attitudes and behaviors. This study aims to understand how different ways of editing health-related messages affect their credibility among adolescents and what impact this may have on the content or format of health information. The sample consisted of 300 secondary school students (M age = 17.26; SD age = 1.04; 66.3% female). To examine the effects of manipulating editorial elements, we used seven short messages about the health-promoting effects of different fruits and vegetables. Participants were then asked to rate the message's trustworthiness with a single question. We calculated second-order variable sensitivity as the derivative of the trustworthiness of a fake message from the trustworthiness of a true neutral message. We also controlled for participants' scientific reasoning, cognitive reflection, and media literacy. Adolescents were able to distinguish overtly fake health messages from true health messages. True messages with and without editorial elements were perceived as equally trustworthy, except for news with clickbait headlines, which were less trustworthy than other true messages. The results were also the same when scientific reasoning, analytical reasoning, and media literacy were considered. Adolescents should be well trained to recognize online health messages with editorial elements characteristic of low-quality content. They should also be trained on how to evaluate these messages.